Immune digital twins for complex human pathologies: applications, limitations, and challenges - Anna Niarakis; Reinhard Laubenbacher; Gary An; Yaron Ilan; Jasmin Fisher; Åsmund Flobak; Kristin Reiche; María Rodríguez Martínez; Liesbet Geris; Luiz Ladeira; Lorenzo Veschini; Michael L. Blinov; et al. (npj Systems Biology and Applications)
Abstract Digital twins represent a key technology for precision health. Medical digital twins consist of computational models that represent the health state of individual patients over time, enabling optimal therapeutics and forecasting patient prognosis. Many health conditions involve the immune system, so it is crucial to include its key features when designing medical digital twins. The immune response is complex and varies across diseases and patients, and its modelling requires the collective expertise of the clinical, immunology, and computational modelling communities. This review outlines the initial progress on immune digital twins and the various initiatives to facilitate communication between interdisciplinary communities. We also outline the crucial aspects of an immune digital twin design and the prerequisites for its implementation in the clinic. We propose some initial use cases that could serve as “proof of concept” regarding the utility of immune digital technology, focusing on diseases with a very different immune response across spatial and temporal scales (minutes, days, months, years). Lastly, we discuss the use of digital twins in drug discovery and point out emerging challenges that the scientific community needs to collectively overcome to make immune digital twins a reality.